Validity of the Novel Radiological Classification System of the Distal Femur - Akkaya, Mustafa; Simsek, Mehmet Emin; Akcaalan, Serhat; Caglar, Ceyhun; Gursoy, Safa; Citak, Mustafa (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Objective Aseptic loosening (AL) is among the most important causes of failure after total knee arthroplasty (TKA). However, while there are numerous underlying causes of AL, the morphometry of the distal femur and intramedullary canal has not been sufficiently demonstrated. This study aimed to show the interobserver and intraobserver reliability and validity of the Citak classification, which has been recently defined according to the morphometry of the distal femur and provides a risk factor definition for AL.Materials and Methods A total of 200 patients whose standardized anteroposterior (AP) and lateral images of the knee joint were obtained between October 2019 and April 2020 were retrospectively evaluated in this study. Patients with a history of extra-articular deformity and knee surgery were excluded from the study. For AL, morphologies of the distal femur were identified by two observers using the new radiological classification system of the distal femur. Mean pairwise Cronbach’s alpha coefficient was used to assess the intra- and interobserver agreement of the classification.Results There was excellent interobserver agreement for the 20 cm proximal and 2 cm proximal to the lateral joint line (PLJL) and adductor tubercle (PAD), respectively. The mean Cronbach’s alpha coefficient was 0.96 (range 0.764–0.944) for the PAD and 0.98 (range 0.734–0.929) for the PLJL. There was also an excellent intraobserver agreement, with 93% average pairwise percent agreement for the index group and 95.5% average pairwise percent agreement for the anatomical classification group.Conclusions The level of inter- and intraobserver agreement for the morphology of the distal femur was excellent in the new radiological classification system, which was shown to be beneficial in the planning of revision knee arthroplasty for AL. However, there is a need for further studies in order to make a correlation of the classification with specific intraoperative findings.
Keywords: distal femur; radiological; classification; morphology